Attitudes and approaches in London boroughs to the use of photographic records in the justification, management and enforcement of tree preservation orders. Issue 4 (2nd October 2017) - Wright, Margaret; Slater, Duncan
Abstract: English law allows a local planning authority (LPA) to impose legal protection for special trees through the making of a tree preservation order (TPO). Against the penalty of criminal prosecution, these orders preserve the appearance of trees for the benefit of public amenity. Current literature and guidance notes disagree on the significance of photographs in the management of protected trees. This study investigated whether there was any variation in approach to the management of photographic records of protected trees by LPAs responsible for the administration of TPOs in 33 London boroughs. It was found that no responding boroughs adopt a formal procedure for the management of photographic records. Analysis of responses (n = 21) indicated that 10 boroughs were photophobic, with their attitude to digital recording technology adversely influencing their working practices. This contrasts with the finding that most officers saw considerable benefit in developing and using a photographic archive of protected trees. It is concluded that current pressure on local authority resources is an obstacle to the capture of such a photographic archive of protected trees, and this, in turn, highlights an opportunity for the creation of a best practice model through tree officer group and governing body cooperation.